Desk Reference on American Government - WETTERAU, Bruce (CQ Press, 2000)
A comprehensive question-and-answer reference that helps readers find accurate answers to a wide range of questions about Congress, the presidency, the Supreme Court, elections, and other aspects of American government. Organized into broad chapters, it covers topics ranging from the Constitution to making laws, from the backgrounds of Supreme Court justices to the vice president's role. Extensively cross-referenced and thoroughly indexed. Annotation copyright Book News, Inc. Portland, Or.